The effect of NH4OH pH on the synthesis of MnFe2O4 as heavy metal adsorbent by using co-precipitation method. (March 2019) - Setiadi, E A; Priyadi, I; Siregar, E M; Tetuko, A P; Kurniawan, C; Achiruddin; Sebayang, P
Abstract: The Fabrications of MnFe2O4 have been completed using co-precipitation method with NH4OH pH variations of 11.7; 12.0; and 12.7. The iron sand and the MnCl2.4H2O powder were mixed using HCl as solvent and NH4OH as setting solution. Then the samples were dried and characterized including: morphology analysis (FE-SEM), powder density, crystal size and structure (XRD), magnetic properties (VSM) and the absorption of Pb and Cu using Atomic Absorption Spectroscopy (AAS). The result of FE-SEM showed that the MnFe2O4 particles were agglomerated. On the other hand, the results of XRD characterization indicated that there is a dominant phase of MnFe2O4. The density powder characterization using a pycnometer suggested that the crystal grain size tends to decrease and the true density tends to increase with the increasing of NH4OH concentrations. The result of VSM showed that the optimum condition was achieved with the addition of NH4OH(pH of 12, 7) where the magnetic properties characterizations indicate that the coercivity value, the magnetic saturation and the magnetic remanence of 1.96 emu/g are 43.82 Oe, 62.78 emu/g, and 1.96 emu/g, respectively. The AAS characterization suggested that the nanoparticles of MnFe2 O4 were able to adsorb heavy metals, (Pb and Cu up to 197 mg/g).